(untitled) (International Journal of Innovative Technologies in Economy, 2019)
The article has considered the ecological component land use of the automobile transport. The main reasons for the negative impact of land use of automobile transport on the environment have been indicated. Their tendency, sources and nature of influence on the use of automobile transport lands have been investigated. The analysis of the harmful in fluence of automobile transport on the vital activity and health of people has been carried out, as well as the data of emissions of harmful substances into the environment have been generated. The dynamics of electric vehicle sales in Ukraine has been presented. A comparative an alysis of economic and environmental efficiency from the use of electric cars and cars on traditional types of fuel, on the example of the brand KIA Soul (Electric) and KIA Soul has been carried out. The pay back period of the use of "green transport" has been calculated. Priority directions for increasing the economic and environmental components of the use of road vehicles has been proposed.